Customary Law as The Basis of Character Education (Study on Indigenous Peoples in Bayan Village, North Lombok) - Yuliatin, Yuliatin; Haslan, Muhammad Mabrur; Sawaludin, Sawaludin (Universitas Negeri Semarang, 2023)
The conditions above illustrate how the Indonesian nation has lost its character as a nation that upholds noble values. However, on the other hand, in a multicultural Indonesian society, some still maintain the existence of noble values inherited by their ancestors. These noble values are guarded and maintained through customary law, which is obeyed with full awareness. Thus, customary law can be the basis for character education, as found in customary law in Bayan Village, North Lombok, and West Nusa Tenggara Province (NTB). The purpose of this study is to describe customary law in Bayan Village, North Lombok, West Nusa Tenggara Province, as a basis for character education. The specific objectives are (1) identification of various types of customary law in Bayan Village as a basis for character education and (2) identification of character values in customary law in Bayan Village. These findings are significant for learning innovations that are contextual and oriented in character strengthening. Data were collected using interviews, observation, and documentation techniques. Data analysis used qualitative analysis with the stages of data reduction, data presentation, verification, and conclusion. The results of the study show that (1) there are various types of customary law in Bayan Village that can be the basis of character education, namely customary law for forest conservation and spring, as well as customary law of Marriage, (2) character values contained in customary law in Bayan village includes: care for the environment, democracy, hard work, and religious. These values are part of the values developed in character education, so they can be the basis of character education.